Assessment of tongue cleaning habit among the patients visiting a dental hospital in Kathmandu - Yadav, Karnika; Poudyal, Sijan; Chaulagain, Rajib; Pradhan, Amita (Nepal Medical College Journal, 2023)
The aim of this study was to assess the tongue cleaning habit among the people to maintain and improve the quality of oral hygiene. This cross-sectional study was conducted in outpatient department of People’s Dental college and hospital, department of Community Dentistry among 312 patients 185 female and 127 male between 18-60 years. The self-administered questionnaire consisted of two parts. The first part consisted of socio-demographic details of participants (age, sex, education and occupation). The second part consisted of 17 questions related to tongue cleanliness behavior. Self-constructed questionnaire adopted from previous study. Data analysis was done by using SPSS 20 version and descriptive statistics were calculated. Out of total 312 participants, 53.8% had a tongue cleaning habits. Sixty nine percent participants cleaned the tongue every day. About two-thirds 65% use toothbrush. Nearly 62% of the participants took 15- 30sec for tongue cleaning. Fifty percent clean the entire tongue. Eighty nine percent started the tongue cleaning about a year ago. Nearly 75% respondent clean tongue on their own without any suggestion from other persons. About 64.3% of the participants were not feeling unpleasant sensation after tongue clean. Nearly more than half 56 % had gagging reflex by using the tongue cleaner. About 53% (n=98) female were having a habit of tongue cleaning. About 30-39 age group 62.1% non-smokers and 57.4% had tongue cleaning habit. About 54.7% drinking tea / coffee had tongue-cleaning habits. In conclusion tongue cleaning habit helps to prevent halitosis, stains, tongue coating and maintain oral hygiene. In this population, more than half reported tongue cleaning habit.